Meningkatkan hasil belajar siswa melalui penerapan model pembelajaran kooperatif tipe GGE pada mata pelajaran PPKn - I Ketut Arumada (Indonesian Journal of Educational Development, 2020)
This action research was carried out at SMA Negeri 1 Marga, with the aim of knowing the improvement of PPKn learning outcomes, through the application of the Group to Group Exchange (GGE) type of cooperative learning model. The research subjects were students of class XI IPS-2 in the academic year 2017/2018 odd semester. While the object of research is the results of learning inthe PPKn KD subject. 3.3 Describing the legal and judicial system in Indonesia in accordance with the 1945 Constitution of the Republic of Indonesia and 4.3 Presenting the results of reasoning about the legal and judicial systems in Indonesia in accordance with the Constitution of the Republic of Indonesia Indonesia 1945. Data on student learning outcomes is obtained through learning outcomes tests. The data analysis was conducted in a descriptive qualitative manner. In this study, the success criteria were determined as follows: (1) the minimum mean value ofstudent learning outcomes was 75%, and (2) classical learning completeness was at least 85%. Based on the results of data analysis, the following results were obtained: (1) in the first cycle, the mean value of learning outcomes reached 70.61 and classical learning completeness was 73.53%; (2) in cycle II, the mean value of learning outcomes reached 78.15 and classical learning completeness was 88.24%. In conclusion, the implementation of the GGE type of cooperative learning model can improve the learning outcomes of students in class XI IPS-2 in the academicyear 2017/2018 odd semester SMA Negeri 1 Marga, Tabanan Regency, Bali. Penelitian tindakan ini dilaksanakan di SMA Negeri 1 Marga, bertujuan untuk mengetahui peningkatan hasil belajar PPKn, melalui penerapan model pembelajaran kooperatif tipe Group to Group Exchange (GGE). Subjek penelitian adalah siswa kelas XI IPS-2 tahun pelajaran 2017/2018 semester gasal. Sedangkan objek penelitian adalah hasil belajar pada mata pelajaran PPKn KD 3.3 Mendeskripsikan sistem hukum dan peradilan di Indonesia sesuai dengan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 dan 4.3 Menyaji hasilpenalaran tentang sistem hukum dan peradilan di Indonesia sesuai dengan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Data hasil belajar siswa diperoleh melalui tes hasil belajar. Analisis data dilakukan secara deskriptif kualitatif. Pada penelitian ini, kriteria keberhasilan ditentukan sebagai berikut: (1) nilai rerata hasil belajar siswa minimal sebesar nilai KKM yaitu 75 dan (2) ketuntasan belajar secara klasikal minimal mencapai 85%. Berdasarkan hasil analisis data, diperoleh hasil penelitian sebagai berikut: (1) pada siklus I, nilai rerata hasil belajar mencapai 70,61 dan ketuntasan belajar secara klasikal sebesar73,53%; (2) pada siklus II, nilai rerata hasil belajar mencapai 78,15 dan ketuntasan belajar secara klasikal sebesar 88,24%. Kesimpulan, penerapan model pembelajaran kooperatif tipe GGE dapat meningkatkan hasil belajar PPKn siswa kelas XI IPS-2 tahun pelajaran 2017/2018 semester gasal SMA Negeri 1 Marga, Kabupaten Tabanan, Bali.